(untitled) (Global Journal of Medical Research, 2022)
Hughes#x2013;Stovin syndrome (HSS) is very rare systemic disorder characterized by the combination of widespread vascular thrombosis and pulmonary vasculitis with serious morbidity and mortality. The exact etiology and pathogenesis of Hughes-Stovin syndrome is unknown. The clinical presentation of Hughes-Stovin syndrome includes hemoptysis, cough, dyspnea, fever and chest pain. Nearly 25% of patients with Hughes-Stovin syndrome develop vascular thromboembolism, arterial aneurysms, and arterial and venous occlusions with nonspecific vasculitis. The vascular lesion was most common in both artery and vein (68%), followed by vein (25%) and artery (8%). We report a case of a 56-years-old male patient presenting with fever of unknown origin. During the diagnostic work up, incidentally found aneurysm formation and thrombosis in the left upper lobe pulmonary artery segmental branch, thrombosis of the right lower lobe pulmonary artery segmental branches.